2022
DOI: 10.26656/fr.2017.6(1).107
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and protein characterization of lima bean (Phaseolus lunatus L) seed

Abstract: Lima bean (Phaseolus lunatus L) is native to Latin America and has spread out worldwide, thus having a high level of diversity. The lima bean seed from a specific region might have different characteristics from others. This study was aimed to characterize the physicochemical and protein of the dry seed of lima bean from Indonesia based on its solubility, electrophoretic pattern, and amino acid profile. The result showed that carbohydrate (68.89±1.55%) was the major component, with starch (41.96±1.10%) as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…In this study, P. lunatus presented similar contents of Fe and Zn as P. coccineus and P. vulgaris, but the concentrations of the other six mineral elements were significantly lower in P. lunatus (Table 4). However, the values of K and P observed for P. lunatus were higher than those observed by Palupi et al (2022), Jayalaxmi et al (2016) and Seidu et al (2015) and the values of P were similar to those reported by Giami (2006) for the same species, although methodological differences may have influenced these results. The species analyzed showed that the variation due to genotype and growth environment or crop location has a significant effect on the grain composition, as was reported for P. vulgaris (Bulyaba et al, 2020;Ribeiro and Maziero, 2022).…”
Section: Mineral Contentssupporting
confidence: 88%
See 2 more Smart Citations
“…In this study, P. lunatus presented similar contents of Fe and Zn as P. coccineus and P. vulgaris, but the concentrations of the other six mineral elements were significantly lower in P. lunatus (Table 4). However, the values of K and P observed for P. lunatus were higher than those observed by Palupi et al (2022), Jayalaxmi et al (2016) and Seidu et al (2015) and the values of P were similar to those reported by Giami (2006) for the same species, although methodological differences may have influenced these results. The species analyzed showed that the variation due to genotype and growth environment or crop location has a significant effect on the grain composition, as was reported for P. vulgaris (Bulyaba et al, 2020;Ribeiro and Maziero, 2022).…”
Section: Mineral Contentssupporting
confidence: 88%
“…Zn and Fe are essential mineral elements for human health and were exceptionally high in the PL-005 and PL-014 populations of P. lunatus, the PC-022 population of P. coccineus and the PV-003 population of the control species P. vulgaris, with 3.88 to 4.49 and 5.62 to 7.38 mg 100 g -1 Zn and Fe, respectively (Table 5). These values are lower than the Fe content reported by Seidu et al (2015) and Palupi et al (2022) in P. lunatus but within the ranges of Fe and Zn in P. vulgaris reported by Herrera-Hernández et al (2018).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Intorasoot (2013) discovered that amino acids with positive charges, such as histidine and lysine, are among those that can inhibit microorganisms. Methionine and cysteine, on the other hand, are present in small amounts in pulse proteins ( Palupi et al, 2022 ). Table 4 presents amino acid composition of protein hydrolysate from various legumes.…”
Section: Amino Acid Composition In Protein Hydrolysate Of Underutiliz...mentioning
confidence: 99%
“…Wild populations of both species are distributed from Mexico to Argentina, presenting a wide range of ecological adaptations. For this reason, it is considered a promising crop to improve food security in predicted scenarios of climate change (Martínez-Reina et al, 2021, Palupi et al, 2022. Four P. lunatus wild gene pools have been defined: two Mesoamerican (MI and MII) and two Andean (AI, AII) (Chacon-Sanchez et al, 2017, Garcia et al, 2021.…”
Section: Introductionmentioning
confidence: 99%